A water-based and metal-free dye solar cell exceeding 7% efficiency using a cationic poly(3, 4-ethylenedioxythiophene) derivative. Issue 6 (14th January 2020) - Bella, Federico; Porcarelli, Luca; Mantione, Daniele; Gerbaldi, Claudio; Barolo, Claudia; Grätzel, Michael; Mecerreyes, David
Abstract : A new cationic PEDOT derivative inhibits repulsion phenomena within iodine-based electrolytes, boosting the efficiency of aqueous solar cells. Abstract : A green, efficient and stable solar cell based only on water and safe and cheap elements of the periodic table is proposed in this work, finally consolidating (also from a sustainability viewpoint) the concept of "artificial photosynthesis" studied for decades by the scientific community. The concept of dye-sensitized solar cells is re-proposed here with a metal-free organic dye, an iodine-based electrolyte in a 100% aqueous environment and a new cathode (cationic PEDOT) synthesized for the first time with the aim of inhibiting the repulsion between the anions of redox couples and the PEDOT:PSS matrix commonly used as the counter-electrode. This elegant setup leads to a record efficiency of 7.02%, the highest value ever obtained for a water-based solar cell and, in general, for a photovoltaic device free of both organic solvents and expensive/heavy metals.